Persepsi Generasi Muda Rumah Tangga Petani terhadap Budidaya Padi Sawah di Subak Piak, Kecamatan Penebel, Kabupaten Tabanan - KURNYANTI, WAYAN NOLY; ASTITI, I WAYAN SRI; DIARTA, I KETUT SURYA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.4, Oktober 2019, 2019)
Perception Of Farmers 'Young Household Generation On Waste Rice Cultivation In Subak Piak,PenebelDistrict, Tabanan Regency The phenomenon of shifting labor in the agricultural sector, on average aged 40 years and over, young workers choose to work in the non-agricultural sector. Tend to choose jobs in sectors that can provide higher wages and are in urban areas. The study aimed to analyze the perceptions of the young generation of farmer households on rice cultivation in Subak Piak, Penebel District, Tabanan Regency. The location determined using deliberate method with qualitative descriptive analysis method. The results of the study that the perception of the young generation of farmer households in terms of social, economic and technical aspects are categorized as good. The social aspect, caring about the existence and sustainability of the subak system and sekaa manyi, plunging into the agricultural sector does not have to be a farmer by becoming a broker, they still think that being a farmer is less prestigious than jobs outside the sector. Economic aspects, the level of income in rice cultivation is not sufficient to meet all the needs of the family requires having a job other than the agricultural sector. Technical aspects, innovation in rice cultivation is needed so that yields increase. Subak Piak can involve the young generation of farmers in various activities such as upakara, ngembak toya, mutual cooperation in cleaning, maintenance of irrigation channels. Youth organizations can become a forum for young people to take part in various activities carried out by subak so that the presence and sustainabilityof subak and other traditional groups can still be  maintained, even though they prefer or have more promising jobs than being farmers.